Apoptosis‐induced cancer cell fusion: a mechanism of breast cancer metastasis. Issue 9 (10th November 2017) - Noubissi, Felicite K.; Harkness, Ty; Alexander, Caroline M.; Ogle, Brenda M.
ABSTRACT: Although cancer cell fusion has been suggested as a mechanism of cancer metastasis, the underlying mechanisms defining this process are poorly understood. In a recent study, apoptotic cells were newly identified as a type of cue that induces signaling via phosphatidylserine receptors to promote fusion of myoblasts. The microenvironment of breast tumors is often hypoxic, and because apoptosis is greatly increased in hypoxic conditions, we decided to investigate whether the mechanism of breast cancer cell fusion with mesenchymal stem/multipotent stromal cells (MSCs) involves apoptosis. We used a powerful tool for identification and tracking of hybrids based on bimolecular fluorescence complementation (BiFC) and found that breast cancer cells fused spontaneously with MSCs. This fusion was significantly enhanced with hypoxia and signaling associated with apoptotic cells, especially between nonmetastatic breast cancer cells and MSCs. In addition, the hybrids showed a significantly higher migratory capacity than did the parent cells. Taken together, these findings describe a mechanism by which hypoxiainduced apoptosis stimulates fusion between MSCs and breast tumor cells resulting in hybrids with an enhanced migratory capacity that may enable their dissemination to distant sites or metastases. In the long run, this study may provide new strategies for developing novel drugs for preventing cancer metastasis.—Noubissi, F. K., Harkness, T., Alexander, C. M., Ogle, B. M. Apoptosis‐induced cancer cell fusion: a mechanism of breast cancer metastasis. FASEB J. 29, 4036‐4045 (2015). www.fasebj.org